The influence of current EU public procurement legislation on the construction industry within the EU - Sedlenieks, Jānis (Riga Graduate School of Law, 2019)
The aim of the master thesis is to identify the role of EU public procurement legislation in ensuring the common market principles in the public procurement procedures within the construction industry. In this thesis, the influence of the EU legislation on the public procurement market of the construction industry will be studied. The most important factors which hinder the involvement of foreign companies in procurement procedures of other member states will be determined and analysed.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Public procurement; construction